Regional Differences In Athroponyms - Seytniyazov K.M. (Euro Asian Journal Publishing, 2024)
The article discusses some patterns of names and territorial diversity of anthropotoponyms, as well as their significance of specific, political and practical significance. Also, on specific examples, their origin and etymology of some anthropotoponyms are studied
Keywords: anthroponyms; anthropotoponyms; geographical object